Stability for grain yield and its contributing traits in bread wheat (Triticum aestivum) - MEENA, H S; KUMAR, DINESH; SRIVASTAVA, T K; PRASAD, S RAJENDRA (The Indian Journal of Agricultural Sciences, 2014)
In a study set of forty seven genotypes of common bread wheat (Triticum aestivum L. emend Fiori & Paol) were evaluated over four years during 2007-08 to 2010-11 to assess the stability of these genotypes for yield and its contributing traits over years and environments. Analysis of variance of stability with respect to 12 traits revealed highly significant variance due to environment for all traits which indicated differential effect of different seasons. The variance for genotypic effect was highly significant for all traits indicating thereby differential response of all the genotypes. Genotype×environment (linear) interaction was also significant for flag leaf length, flag leaf width, peduncle length, grains per spike and 1000-grain weight indicating substantial amount of predictable G×E interaction. Environmental indices indicated that performance of genotypes over four environments varied apparently and environment E2 showed highest favourable impact on grain yield. Varieties K 9107, UP 2382 and PBW 443 were found to be stable across the environments for grain yield and NW 1076 was the highest yielding stable variety in which superior yield was resulted from high mean values of six contributing traits, while variety LOK 1 was the only variety showed stable performance for all 12 traits. The stability of different yield contributing traits varied in compensating manner in different genotypes imparted grain yield stability. The varieties HD 2824, UP 2382, NW 1076, DBW 16, DBW 39, GW 173, HUW 234, NIAW 917, LOK 1, HD 2851 and PBW 154 have shown higher mean values, desirable regression coefficient and non-significant deviation from the regression coefficient for yield and its contributing traits. Based on stability parameters these varieties can be considered as stable performers and may be utilized for hybridization programmes to improve wheat yields.